Inhibition Effect of Essential Oil Extracts on the Corrosion Inhibition of Mild Steel in Chloride-Sulphate Media - Loto, Roland Tolulope; Leramo, Richard; Oyebade, Babatunde (TMS 2019 148th Annual Meeting & Exhibition Supplemental Proceedings, 2019)
Studies on corrosionCorrosioninhibitionInhibition effect of the combined admixture of sage and lavender oil extracts on mild steelMild Steel in dilute H2SO4 and HCl solutions were performed to assess their optimum inhibitionInhibition efficiency at low concentrations through potentiodynamic polarization technique, weight loss analysis and optical image analysis. The surface of the control steelSteel specimen in H2SO4 was subject to severe degradationDegradation, while the steelSteel surface from HCl selectively deteriorated with visible corrosionCorrosion pits. The oil extracts effectively inhibited mild steelMild SteelcorrosionCorrosion in both acids with optimal inhibitionInhibition efficiency of 86.92 and 96.90% in H2SO4, and 84.68 and 97.59% in HCl from potentiodynamic polarization and weight loss analysis. Anodic inhibitionInhibition behavior was the dominant inhibitionInhibitionmechanismMechanism in H2SO4 resulting from molecular coverage of the steelSteel, and cathodic inhibitionInhibitionmechanismMechanism dominated in HCl solution. Thermodynamic calculations showed the extract molecules performed through chemisorption adsorption mechanismMechanism according to Langmuir, Frumkin and Freundlich isotherms.